Evidence for widespread human exposure to food contact chemicals - Geueke, Birgit; Parkinson, Lindsey V; Groh, Ksenia J; Kassotis, Christopher D; Maffini, Maricel V; Martin, Olwenn V; Zimmermann, Lisa; Scheringer, Martin; Muncke, Jane (Journal of exposure science & environmental epidemiology, 2025)
BACKGROUND: Over 1800 food contact chemicals (FCCs) are known to migrate from food contact articles used to store, process, package, and serve foodstuffs. Many of these FCCs have hazard properties of concern, and still others have never been tested for toxicity. Humans are known to be exposed to FCCs via foods, but the full extent of human exposure to all FCCs is unknown. OBJECTIVE: To close this important knowledge gap, we conducted a systematic overview of FCCs that have been monitored and detected in human biomonitoring studies according to a previously published protocol. METHODS: We first compared the more than 14,000 known FCCs to five biomonitoring programs and three metabolome/exposome databases. In a second step, we prioritized FCCs that have been frequently detected in food contact materials and systematically mapped the available evidence for their presence in humans. RESULTS: For 25% of the known FCCs (3601), we found evidence for their presence in humans. This includes 194 FCCs from human biomonitoring programs, with 80 of these having hazard properties of high concern. Of the 3528 FCCs included in metabolome/exposome databases, most are from the Blood Exposome Database. We found evidence for the presence in humans for 63 of the 175 prioritized FCCs included in the systematic evidence map, and 59 of the prioritized FCCs lack hazard data. SIGNIFICANCE: Notwithstanding that there are also other sources of exposure for many FCCs, these data will help to prioritize FCCs of concern by linking information on migration and biomonitoring. Our results on FCCs monitored in humans are available as an interactive dashboard (FCChumon) to enable policymakers, public health researchers, and food industry decision-makers to make food contact materials and articles safer, reduce human exposure to hazardous FCCs and improve public health. IMPACT STATEMENT: We present systematically compiled evidence on human exposure to 3601 food contact chemicals (FCCs) and highlight FCCs that are of concern because of their known hazard properties. Further, we identify relevant data gaps for FCCs found in food contact materials and foods. This article improves the understanding of food contact materials' contribution to chemical exposure for the human population and highlights opportunities for improving public health.
Keywords: Food Contamination; Environmental Exposure; Food Packaging; Biological Monitoring; kontaminace potravin; biologický monitoring; lidé; obaly potravin; Humans; vystavení vlivu životního prostředí